How to Work Smarter, Not Harder When Implementing Check-In/Check-Out. (December 2019) - Weber, Meredith A.; House Rich, Sara E.; Duhon, Gary J.
Check-in/check-out (CICO) is a well-established Tier 2 intervention to address at-risk student behavior problems. Despite its widespread empirical support and applied use, CICO can be taxing for teachers to implement when there is insufficient time available and teacher self-efficacy in addressing behavior problems is low. Evaluation of CICO is necessary to promote smarter decision making and efficient service delivery for students at risk of developing more severe problem behaviors. The discussion article outlines one method to identify the exact amount of Tier 2 support needed to improve an individual student's behavior.